Atlas of the Dominion. Counties of Middlesex, Elgin, Lambton. Province of Ontario. - Walling, Henry Francis, 1825-1888 (Cartographer)
Map showing the counties of Middlesex, Elgin, and Lambton in Ontario, showing plots of land, some of them numbered. Cities and towns, counties, railways, rail stations, ports, post offices, First Nations reserves, and bodies of water are labelled. Page 134 in Atlas of the Dominion. Scale in the lower right reads: six miles to an inch. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .